Analysis of Indonesian Sovereign Green Bond and Green Sukuk Initiatives - Anugrahaeni, Pradina (Badan kebijakan Fiskal, 2017)
AbstractGreen bonds, as a vehicle to mobilize additional investors in supporting sustainable finance, have been a longstanding topic of discussion. Moreover, Green sukuk also have been developed in Islamic jurisdiction markets, mirroring the nature of green bonds in accommodating socially responsible investments. While earlier studies focused on the development of those new asset classes in the developed economies, this paper specifically examines the context of emerging countries, in particular Indonesia. Indonesia is on its way to issue the first green bonds and green sukuk; therefore, it is needed to assure that the initiatives will not disrupt the existing practices. This paper aims to look at the existing Indonesian conventional bond and sukuk markets, then analyse whether the preconditions are sufficient – from financial stability perspectives. Contrary to the Islamic researches, this paper will point out that sukuk practices may not be immune from instability. The paper argues that strong support by the government may serve as a stabilising effect on the policy agenda to launch green bonds and green sukuk in Indonesia. This paper, however, does not scrutiny sukuk structures per case, which may be useful to identify specific issues that may arise.